The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1176/appi.ps.201100529
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Public Stigma of Mental Illness: A Meta-Analysis of Outcome Studies

Abstract: Future research is needed to identify moderators of the effects of both education and contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
1,044
9
31

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,298 publications
(1,197 citation statements)
references
References 89 publications
57
1,044
9
31
Order By: Relevance
“…While a number of concerted efforts such as educational programs and community contact programs have shown some success in decreasing stigma, further studies are needed to identify the most effective ways to decrease mental health related stigma perceived by individuals with mental health concerns, specifically in rural communities [18]. Corrigan, et al, (2012) reviewed outcome studies regarding methods of challenging mental health stigma and concluded that stigma is a local issue and that outreach should meet the needs of individual communities [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of concerted efforts such as educational programs and community contact programs have shown some success in decreasing stigma, further studies are needed to identify the most effective ways to decrease mental health related stigma perceived by individuals with mental health concerns, specifically in rural communities [18]. Corrigan, et al, (2012) reviewed outcome studies regarding methods of challenging mental health stigma and concluded that stigma is a local issue and that outreach should meet the needs of individual communities [18].…”
Section: Discussionmentioning
confidence: 99%
“…Corrigan, et al, (2012) reviewed outcome studies regarding methods of challenging mental health stigma and concluded that stigma is a local issue and that outreach should meet the needs of individual communities [18]. By identifying those most at risk for perceiving stigma in rural communities, efforts can be more appropriately directed and further individualized.…”
Section: Discussionmentioning
confidence: 99%
“…Among the strategies used include social activism, public education, and contact with persons with mental illness. A recent meta-analysis of outcome studies revealed that both education and contact had positive effects on reducing stigma for adults and adolescents with a mental illness (Corrigan, Morris, Michaels, Rafacz, & Rusch, 2012). …”
Section: The Essential Role Of Public Health Policiesmentioning
confidence: 99%
“…Despite the significant challenge of trying to understand the intrinsic relationship between the brain and the mind, neuroscientists have made tremendous strides in piecing together the molecular and genetic complexities governing the cognitive underpinnings of brain function and its infirmities [1]. Nonetheless, myths and stigma still persist in parts of the world regarding patients who are affected by severe mental illnesses such as schizophrenia and affective psychotic disorders [2][3][4]. Besides reducing the patients' access to resources and opportunities (e.g.…”
Section: Introductionmentioning
confidence: 99%